ROMANTIC PIANO ART AESTHETICS AND CLASSICAL PHILOSOPHY ART CORE FUSION PRESENTATION - Feng, Bin (European journal for philosophy of religion, 2023)
In the romantic period, there emerged a lot of piano works with colorful creation methods, which brought people infinite enjoyment of beauty and triggered countless discussions. Starting from the Romantic period, this paper analyzes the aesthetic characteristics of piano art, discusses its aesthetic essence, and traces its development source, aiming to deepen the public's cognition of piano art, strengthen the importance of piano art, give play to the influence of art, let aesthetics penetrate into the public and enrich the emotional experience of the public. Guided by the dialectical materialist philosophy of Hegel, who is the master of classical philosophy, this paper analyzes the philosophical basis of his theory of aesthetic study of piano art and its relationship with the musical language and musical works of romantic piano musicians in the 19th century, and draws a conclusion that the artistic aesthetics of romantic piano and the artistic core of classical philosophy are embodied. The piano works of Romanticism "go back to the inner world" are the double presentation of the music language based on emotion theory and the artistic core of classical philosophy